Captured by Religious Texts: The Jew as a Child in the Merchant of Venice and the Jew of Malta - Hamza Ladjroud (The Journal of Studies in Language, Culture and Society, 2019)
This paper endeavors to revisit William Shakespeare‘s The Merchant of Venice and Christopher Marlowe‘s The Jew of Malta in order to cast more light upon the portrayal of the Jewish characters in both plays. The study intends to re-examine the image of the Jew as a devil-incarnate, capable of all evil deeds such as usury, murder, and treachery. These stereotypes are looked at from a religious perspective, which most probably affords some explanations to whether those images should forever be considered invalid stereotypes, or they are mere manifestations of the commandments of a religious text that a Jew feels most obligated to obey. It‘s therefore our intention to analyze the Jewish characters‘ discourse in relation to the biblical theme of the Jew as a child of God. In so doing, we are likely to reconstruct the image of the Jew from a religious textual background, whose imagination is quixotically captured in the scriptures of the Old Testament and Rabbinic Literature. The article offers an analysis of mainly Shylock‘s and Barabbas‘ rhetoric in accord with theories of captivity as developed and implemented by Garry Ebersole in his authoritative book Captured by Texts: Puritain to Post-modern images of Indian Captivity in an attempt to unearth the ideological roots of Shylock‘s as well as Barabbas‘ religious discourse of separatism and overweening opinion of the Devine Preference of Jews over anything nonJew. Moreover, this type of analysis invites us to approach the bearings of this form of captivity in the light of Freud‘s theory of Jewishness and Totemism, which eventually supports our hypothesis that Shylock and Barabbas were acting and reacting to circumstances on ideological basis; and that their discourse is less likely to have been the result of the aforementioned stereotypes, which were promulgated during the Elizabethan era.